Grouping the Number of Foreign Tourist Visits and Analysis of Tourism Competitiveness in East Java - Laela Faradila Putri Amanda; Avi Budi Setiawan (Efficient: Indonesian Journal of Development Economics, 2024)
Tourist attractions for international visitors are created by foreign tourists. However, East Java Province has failed to attract international tourists to its tourism attractions, resulting in the lowest number of foreign tourist visits to Java Island. East Java Province has the second-fewest foreign tourist visitation in Java after Banten Province. K-Means clustering, and competitiveness monitor analysis are utilized for quantitative research. The K-Means algorithm was used to classify the number of international tourists to East Java Province based on regions and cities that are divided into two clusters: the high cluster (C1), which includes Banyuwangi Regency, Malang Regency, and Surabaya City, and the remaining 35 regions and cities in the low cluster (C2). According to the Competitiveness Monitor (CM), the tourism competitiveness index on the seven indicators is good. It is only that the 0.35-point OI Indicator has not shown good competitiveness. Tourism in East Java Province can compete with international trade with the local government's focus on controlling tourism to earn revenue.